A Theory of Domestic and International Trade Finance - Ahn, JaeBin (IMF Working Papers; Working Paper ;, 2011)
This paper provides a theory model of trade finance to explain the "great trade collapse." The model shows that, first, the riskiness of international transactions rises relative to domestic transactions during economic downturns, and second, the exclusive use of a letter of credit in international transactions exacerbates a collapse in trade during a financial crisis. The basic model considers banks' optimal screening decisions in the presence of counterparty default risks. In equilibrium, banks will maintain a higher precision screening test for domestic firms and a lower precision screening test for foreign firms, which constitutes the main mechanism of the model.